Dynamic risk framework for cascading compounding climate-geological hazards: A perspective on coastal communities in subduction zones - De Risi, Raffaele; Muhammad, Ario; De Luca, Flavia; Goda, Katsuichiro; Mori, Nobuhito (Frontiers in Earth Science, 2022)
Integrated disaster resilience approaches are paramount for enhancing risk management of coastal communities under climate-geological risks. Cascading compounding climate-geological risks are dynamic, interact, and evolve with time. Also, classical convolution of hazard, vulnerability, and exposure does not allow easy implementation of causalities and dependencies that are critical in modelling impact chains due to cascading compounding multi-hazards. A new dynamic multi-hazard catastrophe modelling framework is proposed to fill important research gaps in the temporal evolution of climate-geological risks. Systemic modelling is a key tool where time-dependent and interacting risks are explicitly modelled, and multiple risk metrics can be computed. Furthermore, a possible new entropy-based approach for harmonising risk metrics is presented. Such a harmonisation can facilitate the decision-making process for disaster risk reduction. Finally, a way forward for future implementation of the proposed methodologies is discussed with a focus on the need for the development of new numerical and analytical tools.